How Will Growth in China and India Affect the World Economy? - Dimaranan, Betina; Ianchovichina, Elena; Martin, Will (2012)
China and India are rapidly growing, labor-abundant economies with very different export mixes. China is more integrated into global production sharing for manufactures, while services exports are more important for India. Even assuming India integrates more comprehensively into global production chains, there will be opportunities for rapid growth in both countries. Improvement in the range and quality of their exports can create substantial welfare benefits for the world, and for China and India, and can offset the terms-of-trade losses otherwise associated with rapid export growth. Most countries will need to respond to increased competition in some sectors, and to greater opportunities in others.